Potencial biotecnológico de plantas da Caatinga: atividade antibacteriana e antioxidante de constituintes fixos e voláteis de Vitex gardneriana e Croton piauhiensis - Vale, Jean Parcelli Costa do (2015)
The use of plants for therapeutic purposes is one of the oldest forms of medical practice of humankind. Isolated plant secondary metabolites have contributed significantly to the development of new drugs in recent years. Essential oils, vegetables present, are complex mixtures containing several dozen substances with varied chemical composition and various therapeutic properties. The main objective was to contribute to the scientific knowledge of plant species of the Caatinga with therapeutic potential for development of possible biotechnological products. Were chemically characterized by Nuclear Magnetic Resonance Spectroscopy (NMR) 1H and 13C one and two-dimensional, fixed and volatile secondary metabolites of Vitex gardneriana and volatile secondary metabolites of Croton piauhiensis. It was identified and quantified it is twelve (12) compounds of the essential oil of V. gardneriana, with a predominance of (66.34%) of sesquiterpenes. They were identified and quantified 21 (twenty-one) essential oil compounds from C. piauhiensis, with a predominance of (42.63%) of sesquiterpenes. Was isolated nine (9) fixed constituents V. gardneriana. From the shell VGC (I), a mixture of ursolic acid and oleanolic acid. From the wood: VGL (I) Synthesis of vanillin; VGL (II) p-hydroxy-benzoic acid; VGL (III) 4-hydroxy-3-methoxybenzoate p-hydroxy-benzoic acid (unpublished literature); VGL (IV) acid 2α, 3α, 19α-trihidroxiursan-12-en-28-oic acid and VGL (V) 3-O-β-D-glicopiranosilsitosterol (unprecedented in the literature). From the root: VGR (I) acid protocatechuic; VGR (II) 3-O-β-D-glicopiranosilsitosterol and VGR (III) a mixture of β-sitosterol and stigmasterol. The essential oils and five (5) Secondary metabolites were first tested by checking the antimicrobial activity in the planktonic and biofilm forms, was also checked the antioxidant potential using four different methods. For this purpose, the minimum inhibitory concentration experiments, were conducted, by microdilution technique (MIC) and checked the minimum bactericidal concentration (MBC). As well, as experiments for evaluating the inhibition of the development of biofilm formation by Staphylococcus aureus ATCC 25923 and Pseudomonas aeruginosa ATCC 10145. For this action, the techniques by crystal violet staining and colony forming units were performed. Statistical tests (p <0.05), the comparison between the oil and the negative control was done in the planktonic form, where the essential oil of Croton had an MIC and MBC of 0.15 and 0,62 % (v / v) respectively, for S. aureus. The essential oil of Vitex presented a MIC of 0.31% (v / v), with no significant MBC. However, the oils did not show MIC and MBC for P. aeruginosa in planktonic form. The oil showed significant efficiency in biofilm inhibition assays formed with the respective bacteria, where Croton oil was more efficient than the oil of Vitex. The essential oils of V. gardneriana and C. piauhiensis proved to be capable of inhibiting microbial growth in both forms of bacterial life and showed antioxidant power. As for the secondary metabolites showed no bactericidal properties, however revealed antioxidant activity. In this, context it can be said that fixed and volatile secondary metabolites of C. piauhiensis and V. gardneriana, have the potential to become promising biotech products.